Price structures in the market for long-distance voice telephony in Germany - Gert Brunekreeft; Wolfgang Gross (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 1999)
This paper analyses price structures in the liberalized German market for long-distance telecommunications services. Theoretically deduced patterns are backed-up by empirical observations. The market is exceptionally competitive; entry is taking place on a large scale and prices are falling sharply. The product is strongly homogeneous and search costs are extremely low. Propositions included in the assessment concern the necessary absence of systematic price discrimination, the probability of cut-throat competition, and the necessary presence of a demand-compatible peak-load structure. With respect to the latter there is an observable move of the price structure, which can be explained by regulatory failure.
Keywords: D41; L43; L96; 330; telecommunications; price discrimination; peak-load pricing; Telekommunikationsgebühr; Telefonnetz; Marktstruktur; Betriebliche Preispolitik; Wettbewerb; Theorie; Deutschland